Scopes and opportunities of buffalo farming in Bangladesh: A review (SAARC Journal of Agriculture, 2017)
The present study attempts to examine the scenario of buffalo production in Bangladesh. The buffalo plays a very important role in the South Asian region which constitutes 77.5% of world buffalo population. This region has a great biodiversity in buffalo germplasm, including the world famous source promising buffaloes Murrah and Nili-Ravi - renowned for high milk production potential. It is estimated that about 96.05 % of Asia and 93.19 % of world buffalo milk are produced in South Asian countries. Besides, buffalo milk in South Asian countries is around 54.95 % of the total milk production. The India and Pakistan share 67.99% and 23.96%, of world buffalo milk production respectively. About 71.4% of world buffalo meat is produced in South Asian countries. Although buffalo is an integral part of livestock production system in South Asian countries, it has never been addressed in Bangladesh and always neglected despite their important role in the national economy. In Bangladesh, the total buffalo population are 1.464 million heads that are managed in household subsistence farming as well as extensive free range (Bathan) farming in saline coastal region that are used as a draught animal and partially for milk and meat production. The contribution of buffalo in total milk and meat production in Bangladesh is only 2.0% and 0.94%, respectively. This review has tried to unearth the present scenario of buffalo production in Bangladesh, describing the benefits and values of buffalo milk and meat, advantages of buffalo husbandry over cattle, constraints in buffalo production and recommendations for buffalo development in Bangladesh.SAARC J. Agri., 14(2): 63-77 (2016)